Determination Point of Zero Charge (PZC) of nZVI-MXene Adsorbent for Reduction of Ciprofloxacin Contaminants in Wastewater - Intania Ika Fairuzi; Adhi Yuniarto; Chilyatun Nisa' (Jurnal Serambi Engineering, 2025)
Ciprofloxacin is an antibiotic commonly used for bacterial infections. It is found in significant concentrations in hospital outlet wastewater and the pharmaceutical industry. Nano zero-valent iron (nZVI) has strong reducing power, and MXene is known for its anti-corrosion. Achieving effective results in this adsorption process is influenced by several factors, such as pH. The point of zero charge is the pH at which the material's surface is electrically neutral.The pH pzc was measured by adding the material to a 0.01 M NaNO₃ solution with an initial pH of 2–12, shaking for 2 hours, leaving for 2 days, and measuring the final pH of each solution. The pH pzc on nZVI material is 4.25. The pHpzc of the MXene material is 2.8. The pHpzc on the nZVI-MXene material is 3.45. The pHpzc value on the nZVI-MXene material is lower than nZVI and higher than MXene. The presence of acid groups from MXene, which dominate the surface of the material, can cause the pHpzc value to be closer to the pHpzc value of MXene than nZVI but still higher than MXene due to the influence of the base group from nZVI. In addition to electrostatic interactions, other mechanisms exist during high pH reactions, such as interactions of active functional groups on the material's surface with adsorbates through chemical bonds.